Customer Relationship Management in the Context of Digital Marketing on Customer Satisfaction, Customer Loyalty and Profitability Enhancement at PT. Syntax Corporation Indonesia - Daimah, Daimah (Jurnal sosial dan sains, 2025)
This study aims to analyse the effect or impact of implementing Customer Relationship Management (CRM) in digital marketing strategies on customer relationships in the digital era. With the development of information and communication technology, companies now face new challenges in managing interactions with customers through various digital platforms. This research uses a descriptive analysis approach through a survey to representatives of the Company's marketing team who implement digital-based CRM with customer satisfaction variables, increasing customer loyalty, improving sales performance and increasing Company profitability. The results show that the implementation of digital-based CRM can positively improve communication efficiency, service personalisation, and more optimal customer data management, which in turn contributes to increased satisfaction, loyalty, performance and profitability. In addition, the findings also reveal that the use of digital marketing tools, such as social media, email marketing, and chatbots, further strengthens companies' relationships with customers. The research suggests that companies leverage digital CRM technology integrated with digital marketing platforms to maximise customer experience and achieve more effective marketing goals.